Analyzing the Types and Implementation of Elicitation Strategies in English Classroom at Al Islam Boarding School - Ikhlas Abdi Perkasa (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to examine the elicitation strategy used by English teachers at Al-Islam Boarding School as well as the perception of teachers and students on its effectiveness. The background of this research is the dominant use of Arabic in the school environment, which limits students' opportunities to practice speaking in English. The limitations of learning media such as projectors and language laboratories also require teachers' creativity in encouraging student participation. Although the teachers were not familiar with the theoretical term "elicitation," the results of the observations showed that they intuitively applied a variety of strategies to provoke students to speak. This study used a qualitative case study design with purposive sampling technique, involving four teachers and four students from classes X and XI. Data was collected through classroom observation, lesson plan analysis, and in-depth interviews. The findings showed that all teachers used WH-questions as the main basis of the elicitation strategy, which were then varied with inferential questions and speech prompts according to their respective pedagogical goals. Grade X teachers place more emphasis on student comfort and motivation through the use of visuals and games, while grade XI teachers implement more complex strategies to encourage high-level thinking and grammatical accuracy. Students' perceptions confirm that clear context, visuals, and games increase their confidence in speaking. This study concludes that teachers are able to apply elicitation strategies adaptively despite limited resources.